UPAYA PENINGKATAN HASIL BELAJAR SISWA MELALUI MODEL PEMBELAJARAN COOPERATIVE LEARNING TIPE TEAM GAME TOURNAMENT (TGT) PADA MATA PELAJARAN MATEMATIKA KELAS V SD NEGERI NGALIYAN 03 - Faridatul Munawaroh; Fitria Dwi Prasetyaningtyas; Filiana Dian Arlinda (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The research entitled "Efforts to Increase Student Learning Outcomes Through the Team Game Tournament (TGT) Type Cooperative Learning Model in Mathematics Class V at Ngaliyan 03 Elementary School" was motivated by the low learning outcomes of fifth grade students in mathematics. This was known when carrying out learning practices in the class and based on interviews with class teachers, therefore this classroom action research was carried out. The formulation of the problem in this study is whether the Cooperative Learning model of the Teams Games Tournaments (TGT) type can improve mathematics learning outcomes in fifth grade students of SD NNgaliyan 03?. Thegoal to be achieved in this study is to improve mathematics learning outcomes through the Teams Games Tournaments (TGT) Cooperative Learning model for fifth grade students at SD N Ngaliyan 03. This type of research is collaborative classroom action research (PTKK). The population of this study were all fifth grade students at SD Negeri Ngaliyan 03. After conducting this collaborative class action research, it was found that learning outcomes and student learning presentations increased. Based on the results of this study, the suggestions given are to use a learning model that can accommodate students with different abilities andwork in a funand enthusiastic way.